Algunas observaciones en torno al título 39 de la Eisagoge de Focio - Andrés Santos, Francisco Javier (Scritti per Alessandro Corbino, 2016)
The article referes to some aspects of the title 39 of Photius Eisagoge, dealing with several conceptual problems of the property law in Byzantine Empire in 9th and 10th centuries, namely the real meaning of the work koinotomia in this work and its relationship with the Roman opus novum and other institutions of the praedial servitudes. This matter can also offer some interesting remarks on the reception of Roman legal texts in the Byzantine law tradition.